Manual de funcionamiento, mantenimiento y aplicación pedagógica del equipo (horno deshidratador, coccionador y ahumador) en el laboratorio de investigacion en cárnicos de la carrera de Agroindustria en la Universidad Técnica de Cotopaxi. - Bermeo Zapata, Mariana Lizbelia (2022)
The meat research laboratory of the Agroindustry Career of the Technical University of Cotopaxi has high-tech equipment to facilitate the student learning through practices that are led by the teachers in charge, taking into account the rules stablished within the laboratory, using the appropriate clothing and applying the theoretical in practice. In the present research work, a manual of operation, maintenance and pedagogical application of the dehydrator cooker and smoker oven was elaborated that will help to have a document that allows the proper handling to facilitate the useful life of the equipment. For the preparation of the document, different types of research were used, of which we can mention: documentary, descriptive and bibliographic research, subsequently different research instruments were applied among which we mention: technical sheets and observation sheets, which lead to carry out this project in an appropriate way. A manual of operation, maintenance and pedagogical application was carried out, in which the generalities, characteristics, parts, requirements, on and off, mode of operation of the equipment, the different types of maintenance in which we cite: routine, preventive, corrective; staff safety measures, this will improve the teaching-learning process for the execution of practices in the laboratory. Based on the practice carried out on the realization of the smoked Frankfurt sausage, the correct functioning of the dehydrator, cooker and smoker oven was demonstrated.